Delusion, reality, and intersubjectivity: a phenomenological and enactive analysis - Fuchs, Thomas (Philosophy, psychiatry, & psychology, 2020)
According to current representationalist concepts, delusion is considered the result of faulty information processing or incorrect inference about external reality. In contrast, the article develops a concept of delusion as a disturbance of the enactive and intersubjective constitution of a shared reality. A foundation of this concept is provided by a theory of the objectivity of perception, which is achieved on two levels: 1) On the first level, the sensorimotor interaction with the environment implies a mobility and multiplicity of perspectives that relativizes the momentary point of view. 2) On the second level, the social interaction with others implies a virtual shifting and contrast of perspectives which helps to overcome a merely subject-centered worldview through participatory sense-making. On this basis, the alteration of experience in beginning psychosis is phenomenologically described as a subjectivization of perception, resulting in an overall experience of self-centrality and derealization. Delusion then converts the disturbance of perception into a reframing of the perceived world, namely an assumed persecution by mundane enemies. Through this, a new sense-making is established, yet in a way that is fundamentally decoupled from the shared world. The possibility of intersubjective understanding is thus sacrificed for the new coherence of the delusion. Further implications of the loss of the intersubjective co-constitution of reality are analyzed, in particular related to disturbances of communication.